2020
DOI: 10.3892/ijmm.2020.4709
|View full text |Cite
|
Sign up to set email alerts
|

circRNA RNF111 regulates the growth, migration and invasion of gastric cancer cells by binding to miR‑27b‑3p

Abstract: hsa_circ_0001982 [circRNA ring finger protein 111 (RNF111)] has been found to promote cancer growth; however, its role in gastric cancer (GC) remains unclear. The present study examined the effects of circR-RNF111 on the growth, migration and invasion of GC cells and aimed to elucidate the underlying molecular mechanisms. The expression levels of circR-RNF111 and miR-27b-3p in GC tissues and GC cell lines were detected by reverse transcription-quantitative PCR (RT-qPCR). StarBase v2.0 and dual-luciferase assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Deng et al demonstrated the oncogenic role of circ_0001982 in colorectal cancer development through sponging miR-144 [ 16 ]. Moreover, Wang et al uncovered that circ-RNF111 sponged miR-27b-3p to aggravate GC cell growth and metastasis and repress apoptosis [ 17 ]. Corresponding to the previous studies, we also demonstrated the promotional effect circ-RNF111 in GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deng et al demonstrated the oncogenic role of circ_0001982 in colorectal cancer development through sponging miR-144 [ 16 ]. Moreover, Wang et al uncovered that circ-RNF111 sponged miR-27b-3p to aggravate GC cell growth and metastasis and repress apoptosis [ 17 ]. Corresponding to the previous studies, we also demonstrated the promotional effect circ-RNF111 in GC.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of circRNAs in GC has also been widely explored [ 12 14 ]. CircRNA ring finger protein 111 (circ-RNF111, hsa_circ_0001982) was identified as an oncogene in breast cancer [ 15 ], colorectal cancer [ 16 ] as well as GC [ 17 ]. Even so, the functions and regulatory mechanisms of circ-RNF111 remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs were discovered to exert competing endogenous RNA (ceRNA) for miRNAs in cancer [ 7 ]. For instance, circRNA RNF111 is the ceRNA for miR-27b to promote gastric cancer proliferation [ 16 ]. Circ-ZNF652 is the ceRNA for miR-29a to enhance liver cancer growth and metastasis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a class of non-coding, single-stranded small RNAs (microRNAs (miRNAs)) have been suggested to have regulatory functions during post-transcriptional stages in many physiological processes [ 22 ]. miRNAs play an important role in the active regulation of cellular and biological processes, such as cell migration [ 23 , 24 ], apoptosis [ 25 ], proliferation [ 26 , 27 ], and metabolism [ 28 ]. Multiple studies have demonstrated that aberrant miRNA expression in female reproductive tissues/cells and embryos is related to disordered folliculogenesis and GC proliferation [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%